Spin-orbit treatment of UV-vis absorption spectra and photophysics of rhenium(I) carbonyl-bipyridine complexes: MS-CASPT2 and TD-DFT analysis - Heydová, Radka; Gindensperger, Etienne; Romano, Roberta; Sýkora, Jan; Vlček, Jr, Antonín; Záliš, Stanislav; Daniel, Chantal (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2012)
The lowest-lying spectral transitions in [ReX(CO)(3)(bpy)] (X = Cl, Br, I; bpy = 2,2'-bipyridine) complexes were calculated by means of spin-orbit time-dependent density functional theory (SO-TD-DFT) and spin-orbit multistate complete active space second-order perturbation theory (SO-MS-CASPT2). Computational results are compared with absorption spectra measured in different solvents and used to qualitatively explain the temperature dependence of the phosphorescence decay parameters that were measured for the whole series of complexes. Spin-orbit excited-state calculations interpret their electronic absorption spectra as arising from a bunch of spin mixed states with a singlet component of only 50-90% (depending on the halide), and attribute the phosphorescence decay to thermal population of spin-mixed states with a substantial singlet character.